Correlation between mortality due to COVID-19, wealth index, human development and population density in districts of Metropolitan Lima during 2020: Correlación entre mortalidad por COVID-19, índices de riqueza y desarrollo humano y densidad poblacional en distritos de Lima Metropolitana durante el 2020 - Dorregaray Farge, Zalia E. (2021)
OBJECTIVE: To determine the correlation between mortality due to COVID-19 and incidence of poverty and district human development index (HDI) in the department of Lima. METHODOLOGY: An observational, ecological, correlational study. The population were patients who died from COVID-19 in Lima Metropolitana. We included all patients reported dead in the open data base of the Ministerio de Salud. The dependent variable was mortality due to COVID-19, calculated by dividing the number of deaths by the total district population, and the independent variables were the incidence of poverty and HDI. We carried out a secondary analysis evaluating the fatality by COVID-19. The correlation was calculated through Spearman’s non-parametric method. RESULTS: 13 154 people died of COVID-19 during the period between March and September, the majority was of masculine gender with an average age of 66 years. We did not find a significant correlation between mortality and incidence of poverty (rho=-0,2230; p=0,15). We found a significant correlation between mortality due to COVID-19 and HDI (rho= 0,4466; p=0,002). Mortality was correlated with population density (rho=0,7616; p=<0,001). We found a positive (rho=0,32) and significant (p=0,037) correlation between fatality and incidence of poverty. We found a significant correlation between fatality due to COVID-19 and population density (rho=0,7616; p=<0,001). We did not find a significant correlation between fatality and HDI. CONCLUSIONS: Population density was a factor associated in the most consistent manner with mortality and fatality due to COVID. Poverty was associated to greater fatality, but not to greater mortality.